Pengetahuan dan Sikap Masyarakat terhadap Penerimaan Vaksin Covid-19 - Hanggara Yonatriza; Aniska Indah Fari; Maria Tarisia Rini (Universitas Baiturrahim, 2023)
The covid-19 vaccine is given to provide immunity for community groups against the transmission of covid-19. Public knowledge about the COVID-19 vaccine is still lacking and there are still many people's attitudes that are reluctant to be vaccinated against COVID-19. These two things cause the low coverage of the COVID-19 vaccine in Indonesia. Objective: to find out the relationship between knowledge and public attitudes towards the covid 19 vaccine. Methods: The type of research used is quantitative with the use of descriptive survey methods. The sampling technique used was total sampling. The sample in this study were 85 respondents. Collecting data using a questionnaire. Bivariate analysis uses the Kendall's tau test . The results showed that the median value of the respondent's age was 42 years, most of the respondents were female with a total of 51 respondents (60%). Most of the respondents' occupations are housewives with 36 respondents (42.4%). The education of the most respondents is SMA with a total of 42 respondents (49.4%). Knowledge of respondents is known to be moderate with a total of 61 respondents (71.8%). The attitude of the respondents is known to be good with a total of 56 respondents (65.9%), getting the complete vaccine as many as 52 respondents (61.2%). Bivariate analysis showed that there was a significant relationship between knowledge and acceptance of the covid 19 vaccine (π : 0.255 p : 0.017) and significant relationship between attitude and acceptance of the covid 19 vaccine (π: 0,944 p : 0, 007)